2010
DOI: 10.5539/ijms.v2n1p175
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shopping Orientation and Store Image on Patronage of Furniture Store

Abstract: Knowledge on furniture consumers' retail patronage will promote and enhance efforts to increase sales at furniture stores and could guide future research. This research therefore was proposed to develop a general model of retail patronage and to empirically test the relationships proposed in the model in the context of furniture market. The objectives of the study include 1) is to review existing retail patronage models and related literature 2) to develop a general framework of retail patronage behavior and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 28 publications
3
28
0
2
Order By: Relevance
“…They have also concluded that the concept of shopping orientation consists of "a personal dimension (e.g. activities, interests, opinions, motives, needs and preferences) Hassan, Muhammad & Bakar (2010) consider simply that this concept is related to general predisposition toward acts of shopping.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have also concluded that the concept of shopping orientation consists of "a personal dimension (e.g. activities, interests, opinions, motives, needs and preferences) Hassan, Muhammad & Bakar (2010) consider simply that this concept is related to general predisposition toward acts of shopping.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From previous studies, such as [51,52] etc., this study deduces four factors: convenience, product, atmosphere, and location. Hence the shop and commercial district selection attributes relevant to government business support are as follows: convenience [20,40,[53][54][55], product [20,27,40,[55][56][57], store atmosphere [40,48,55,58,59] and location [20,37,39,40,48,55,[60][61][62].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is assumed that the high-income level and expenditure size are because of high accessibility as key shop attributes [37,39] and shopping convenience [64,65] accompany consumer awareness about product factors [57,64,66].…”
Section: Characteristics Analysis Per Support Type (Mnl)mentioning
confidence: 99%
See 2 more Smart Citations